Improving Emergency Dental Raediography Response Times Through Coordination Between Dentists And Their Assistants Together With Patient Care Technicians, And Radiology Staff (The Review of Diabetic Studies, 2024)
Emergency dental radiography plays a crucial role in the accurate and timely diagnosis of traumatic dental injuries, odontogenic infections, and maxillofacial emergencies that can progress rapidly if not evaluated correctly. Despite advances in digital imaging and structured workflow design, delays in obtaining radiographs remain a major barrier to effective emergency dental care worldwide, often prolonging patient pain, increasing diagnostic uncertainty, and contributing to unnecessary complication rates. This comprehensive review assesses the significance of rapid radiographic response in dental emergencies and explores the coordinated roles of dentists, dental assistants, patient care technicians (PCTs), and radiology personnel in improving workflow efficiency, imaging accuracy, and patient outcomes. Global and national evidence—including health system quality transformation efforts within Saudi Vision 2030—emphasizes that an integrated model supported by healthcare communication technology, interdisciplinary training, and standardized imaging protocols significantly reduces response times and enhances continuity of care. The paper concludes with a framework for optimized emergency dental radiography response, emphasizing the synchronization of staff roles and digital workflow innovations to ensure timely diagnosis and appropriate intervention.